Prevalence of Postural Issues and Associated Risk Factors among House Officers: A Cross-sectional Study - Saba Waheed; Tarim Nayab; Maristella Masi; Fatima Fatima; Muhammad Zair Khan; Afshan Ahmed (Archives of Current Research International, 2025)
This study aimed to investigate the association between common faulty postures and their risk factors among 147 house officers at Dow University of Health Sciences. Data were collected using a posture analysis form and analyzed with SPSS version 22 over six months. Informed consent was obtained prior to postural assessments, which included general physical evaluation and a plumb line test. Six common faulty postures were evaluated: forward head posture, lordosis, kyphosis, scoliosis, uneven shoulder height, and back muscle hump. The sample size was determined using Open Epi software. Forward head posture was the most prevalent faulty posture (76.9%), followed by lordosis (28.8%), while scoliosis was the least common (7%). The chi-square test was used to analyze the relationship between postures and working hours. Forward head posture (p = 0.05) and uneven shoulder height (p = 0.002) showed statistically significant associations with working hours. However, no significant associations were found for lordosis (p = 0.85), kyphosis (p = 0.07), or scoliosis (p = 0.32). These findings highlight the potential impact of working hours on specific postural deviations.